Mecp2 Mediates Experience-Dependent Transcriptional Upregulation of Ryanodine Receptor Type-3 - Torres, Rodrigo F.; Hidalgo, Cecilia; Kerr, Bredford (Frontiers in Molecular Neuroscience, 2017)
Mecp2 is a DNA methylation reader that plays a critical role in experience-dependent plasticity. Increasing evidence supports a role for epigenetic modifications in activity-induced gene expression. Hence, candidate genes related to such phenomena are of great interest. Ryanodine receptors are intracellular calcium channels that contribute to hippocampal synaptic plasticity, dendritic spine remodeling and participate in learning and memory processes. Here we exposed mice to the enriched environment (EE) paradigm, which through increased stimulation induces experience dependent-plasticity, to explore a role for methyl-cytosines and Mecp2 in directing Ryanodine receptor 3 (Ryr3) transcriptional activity. EE induced a hippocampal-specific increase in the methylation of discrete cytosines located at a Ryr3 isoform promoter; chromatin immunoprecipitation experiments revealed that EE increased Mecp2 binding to this Ryr3 isoform promoter. Interestingly, the experimental paradigm induced robust Ryr3 upregulation, accompanied by miR132-dependent suppression of p250GAP, a pathway driving synaptogenesis. In contrast to WT mice, Mecp2-null mice showed diminished levels of Ryr3 and displayed impaired EE-induced Ryr3 upregulation, compromising miR132 dependent suppression of p250GAP and experience-dependent structural plasticity. Based on these results, we propose that Mecp2 acts as a transcriptional activator of Ryr3, contributing to experience-dependent plasticity.